Economics Without Borders 2017
DOI: 10.1017/9781316636404.005
|View full text |Cite
|
Sign up to set email alerts
|

Population, Migration, Ageing and Health: A Survey

Abstract: We review the literature on recent demographic changes in Europe, focusing on two of the main challenges brought about by an ageing population: severe labour shortages in many sectors of the economy and growing pressures on both health and welfare systems. We discuss how and to what extent migration can contribute to addressing these challenges both in a short and a long-term perspective. Finally, we identify several areas in which more research is needed to help devise more effective policies to cope with a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…Thus, nowadays, the social public health support system has suffered, due to plummeting healthcare and social contributions paid by the ever-shrinking working age population. This allotment of funds is particularly dedicated to older people, whose need for healthcare activities is far larger than those of the young [ 7 , 20 , 21 , 22 , 23 ]. This applies also to the recovery after a COVID-19 infection [ 10 , 23 ] (p. 3), which has shown that, no matter the origin, well-being, gender, or culture, that “health is regarded as the most important asset for active ageing”.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…Thus, nowadays, the social public health support system has suffered, due to plummeting healthcare and social contributions paid by the ever-shrinking working age population. This allotment of funds is particularly dedicated to older people, whose need for healthcare activities is far larger than those of the young [ 7 , 20 , 21 , 22 , 23 ]. This applies also to the recovery after a COVID-19 infection [ 10 , 23 ] (p. 3), which has shown that, no matter the origin, well-being, gender, or culture, that “health is regarded as the most important asset for active ageing”.…”
Section: Brief Literature Reviewmentioning
confidence: 99%
“…In this context, to our purposes, it is worth mentioning four contributions: from the theoretical point of view, the stimulating interdisciplinary approach suggested by Brettell and Hollifield (), which present different approaches to central concepts of international migration; from the empirical point of view, the work developed by Helbling and Michalowski (), who reviewed the most recent literature at the forefront of index‐building to explain the coming into being and effectiveness of immigration and citizenship policies; from the policy oriented point of view, the proposals advanced by Delgado Wise, Márquez Covarrubias, and Puentes (), who provided some key elements for reframing the debate on migration, development, and human rights with particular emphasis on the promotion of a comprehensive, inclusive, and human‐centred alternative agenda. Finally, more specifically from the geographical point of view, of primary interest to our study, Dustmann, Facchini, and Signorotto () review the literature on recent demographic changes in Europe, focusing on two of the main challenges brought about by an ageing population: severe labour shortages in many sectors of the economy and growing pressures on both health and welfare systems. They discuss how and to what extent migration can contribute to addressing these challenges both in a short and a long‐term perspective and they identify several areas in which it is urgent to devise more effective policies to cope with an ageing society.…”
Section: Literature Reviewmentioning
confidence: 99%